Concordance of Blood-Based and Normal Tissue-Based Dihydropyrimidine Dehydrogenase (DPYD) Genotyping. (24th March 2022) - Morelli, Cristina; Formica, Vincenzo; Doldo, Elena; Riondino, Silvia; Rofei, Michela; Vergilii, Lorena; Palmieri, Giampiero; Arkenau, Hendrik-Tobias; Roselli, Mario; Orlandi, Augusto
Abstract : In response to the recently published article by Sharma et al, this letter to the editor presents data about the concordance of blood and normal tissue-based evaluation of DPYD genotyping that suggests that pharmacogenetic screening could be contextual to tumor molecular profiling.